Ivan Petrovych Dzyub (to the 90th anniversary of his birth) - Brodin, M.S.; Zagorodny, A.G.; Lev, B.I.; Naumovets, A.G.; Bryzhyk, L.S.; Zasenko, V.I.; Zolotaryuk, O.V.; Kukhtin, V.V. (Ukrainian Journal of Physics, 2024)
In March this year, the scientific community celebrates the 90th anniversary of the birth of Ivan Petrovych Dzyub, a well-known Ukrainian theoretical physicist, the first chairman of the Higher Attestation Commission of independent Ukraine, a diplomat, a well-known interpreter and public figure, a member of the National Union of Writers of Ukraine, the laureate of the State Prize of the Ukrainian SSR in science and engineering, the laureate of the Maksym Rylskyi Prize, and a knight of the Order of the Rising Sun, Gold Rays with Rosette (Japan).